Hygiene dan Sanitasi Desa Wisata: Peningkatan Kualitas Air Sumur Melalui Media Filterisasi, Pangkajene dan Kepulauan: Tourism Village Hygiene and Sanitation: Well Water Quality Improvement through Media Filterization, Pangkajene and Islands - Astuti, Harlina Putri; Rusli, Afdol; Dos Santos, Hezron Alhim; Aryadhi, Alvin; Anugrah, Aksan; Latihfa, Latihfa (Politeknik Pariwisata Makassar, 2024)
Poor well water quality is a problem often faced by rural communities in Indonesia. This community service activity aims to improve the quality of well water in Taraweang Village through the use of simple filtering equipment. Through training and demonstrations, the community of Taraweang Village managed to improve their understanding and skills in managing well water using filtering technology. The results of this activity showed a significant improvement in well water quality, including a decrease in iron, manganese and bacteria levels in the water. The success of this program opens up opportunities for replication in other villages experiencing similar problems, with a note that continuous monitoring and support are needed to ensure the sustainability of the use of this technology